The Effectiveness of a Deep Listening Strategy through Problem-Based Listening Tasks on First-Year University Students’ Listening Competence - Fathur Rohman (Jurnal Pendidikan Edutama, 2026)
This study investigated the impact of implementing a Deep Listening strategy through Problem-Based Listening Tasks (PBLT) on the listening competence of first-year university students. A quasi-experimental method employing a pretest–posttest control group design was applied to 42 students divided into experimental and control groups. Data were collected using a listening comprehension test and a cognitive engagement observation instrument. The findings reveal that students exposed to the Deep Listening–PBLT approach achieved substantially higher listening gains than those receiving conventional instruction. The most notable improvements occurred in inferential comprehension and information integration skills. Statistical analysis confirmed a significant difference between groups with a large effect size. These results indicate that integrating deep listening practices with problem-based tasks provides an effective pedagogical approach for enhancing listening competence in higher education contexts.